Pola Mengajar Sekolah Minggu Buddha - Arief Gunawan; Catur Feri (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Dhammasekha students as part of the citizens of the Republic of Indonesia. The nationalism of every citizen needs to be continuously developed. Students as the nation's next generation need education to instill nationalism. One of the things that can be done is to study and practice the teachings of the religion that is adhered to properly and correctly. Buddhist storytelling is one of the language skills that students of the Dhammasekha School need to have. Through Buddhist storytelling skills can foster a sense of nationalism for students. Based on the background description above and considering the importance of Buddhist storytelling skills to foster a sense of nationalism, the authors are interested in studying “The Role of the Dhammasekha Surya Jaya School Teacher in Instilling a Sense of Nationalism Through Buddhist Storytelling Skills.